Vertical jump performance in Italian elite trials athletes - Albano, D.; Coppola, S.; Vastola, R. (Journal of Physical Education and Sport, 2019)
This research aims to provide data on explosive and reactive strength characteristics of Italian elite Trials athletes, through vertical jump tests. Five elite athletes (age: 19.6±3.3 y; height: 1.80±0.04 m; body mass: 71.7±7.4 kg) all participating in the Trials World Cup, performed the squat jump and the countermovement jump tests. The height of the jumps was measured using the OptoJump Next (Microgate, Bolzano, Italy). The height of the jump was obtained, then the eccentric utilization ratio (EUR) was calculated as a ratio between the heights of CMJ and SJ, mean and standard deviation of the sample were obtained through a descriptive statistical analysis. Furthermore, a comparison was made between the values obtained and values found in the scientific literature for elite athletes from other sports. From research carried out exclusively data on high-level athletes and performed with OptoJump technology were collected, all studies not corresponding to these criteria were excluded from the analysis. The results show that the Italian elite Trials athletes have good explosive and reactive strength as shown in the SJ (41.0 ± 2.4cm) and in the CMJ (44.0 ± 4.5cm), they also display good performance in comparison to athletes of the same level in other sports, similar to those of hurdlers and volleyball players, also the EUR above 1 (1.07 ± 0.5) suggests that they are well-trained athletes. The results obtained, although on a small sample, provide useful data to describe the athletic profile of Italian elite Trials athletes and could help coaches to structure training programs adapted to the specific demands of this sport.